Interpretation of Humanistic Ideas in the Views of the Mystic Mashrab - Soatov Rasul (Genius Journals, 2022)
In this scientific article, the study of the humanist ideas in the socio-philosophical views of the Uzbek poet and thinker, mystic and Sufi Mashrab, the universal views of the poet such as humanity, justice, and patriotism were analyzed.
Keywords: Kaaba; Shah Mashrab; east; Allah